Long noncoding RNA network for lncRNA-mRNA interactions throughout swine estrous cycle reveals developmental and hormonal regulations in reproductive tissues - Yoon-Been Park; Chiwoong Lim; Byeonghwi Lim; Jun-Mo Kim (Journal of Animal Science and Technology)
The mechanism of estrous cycles of pigs should be explored because their reproductive traits are useful for manipulating productivity and solving problems such as infertility. These estrous cycles should be elucidated to understand the complex interactions between various reproductive tissues (including the ovary, oviduct, and endometrium) and the complex range of hormone secretions during estrous cycles. Long non-coding RNAs (lncRNAs) regulate target genes at transcriptional, post-transcriptional, and post-translational regulation levels in various species. However, unlike mRNAs, lncRNAs in pigs have not been sufficiently annotated, and understanding the protein level of coding genes has limitations in determining the mechanism of the reproductive traits of porcine. In this study, the lncRNAs of the porcine ovary, oviduct, and endometrium were investigated on days 0, 3, 6, 9, 12, 15, and 18 of the estrous cycle. In addition, the characteristics and functions of the identified lncRNAs were explored. 19,021 novel lncRNA transcripts were selected, and the comparison of the characteristics of the newly identified lncRNA and mRNA showed that similar to those of previous studies. Four lncRNA networks were chosen through network analysis. The cis-acting genes of lncRNAs included in each network were identified, and expression patterns were compared. The main lncRNAs (XLOC_021792, XLOC_017111, ENSSSCG00000050977, XLOC_000342, ENSSSCG00000050380, ENSSSCG00000045111, XLOC_008338, XLOC_004128, and ENSSSCG00000040267) were determined from the network by considering the cis-acting genes. Specific novel lncRNAs were discovered in the reproductive tissues during the swine estrous cycle, and their time-serial expression dynamics were confirmed. As the main lncRNAs are involved in the development of each reproductive tissue and hormone action, they can be utilized as potential biomarkers to help improve and develop the reproductive traits of pigs.